OPTIMASI PENGOPERASIAN EMBUNG HUTAN PANTANG UNTUK MEMENUHI KEBUTUHAN AIR IRIGASI PADA DAERAH IRIGASI CUBO TRIENGGADENG KABUPATEN PIDIE JAYA - Ifrayaski Ifrayaski; Azmeri Azmeri; Syamsidik Syamsidik (Prodi Magister Teknik Sipil Unsyiah, 2019)
The Cubo Trienggadeng Irrigation Schme in Pidie Jaya District fulfills irrigation water depending on the Cubo Trienggadeng Dam which has a fluctuating discharge. The Cubo Trienggadeng Irrigation Scheme divides three technical rotation zones to avoid water user conflicts. In the growing season, rendeng planting season can irrigate the entire rice field area of the Cubo Trienggadeng Irrigation Scheme, while during the gadu planting season (May to August) it can only irrigate an area of 428,25 Ha of rice fields in zone I of a total functional area of 1.090 Ha. To fill irrigation water there are reservoirs in the zone II area which can provide water deposits as reserves with Hutan Pantang small dam. The source of the small dam is from rainwater harvesting, because there is no inflow that enters the reservoir. The primary data in this study is by observing small dam, irrigation area and irrigation network and measuring the dimensions of the carrier channel while secondary data obtained from previous studies and other related institutions, namely technical data on small dam, rainfall, irrigation network schemes. The optimization technique model is used to solve the problems , this study uses non-linear programs with Microsoft Excel solver. In reservoir optimizing for service area, it is expected to be able to solve the problem. The service area of Hutan Pantang small dam covers 84,25 Ha, which requires the largest discharge rate of 0,19 m3 / sec with a water surface height of 1,77 m and a volume of reservoir 278,161.66 m3 capable of operating 100% to meet reliability. The results achieved are optimal small dam operation, where the reliability of small dam affects the volume of the reservoir